Products of the porcine group C rotavirus NSP3 gene bind specifically to double-stranded RNA and inhibit activation of the interferon-induced protein kinase PKR. - Langland, J O (1994)
The porcine group C rotavirus (Cowden strain) NSP3 protein (the group C equivalent of the group A gene 7 product, formerly called NS34) shares homology with known double-stranded RNA-binding proteins, such as the interferon-induced, double-stranded RNA-dependent protein kinase PKR. A clone of NSP3, expressed both in vitro and in COS-1 cells, led to the synthesis of minor amounts of a product with an M(r) of 45,000 (the expected full-length M(r) of NSP3) and major amounts of products with M(r)s of 38,000 and 8,000. Restriction enzyme digestion analysis prior to expression in vitro and amino-terminal sequence analysis suggest that the products with M(r)s of 38,000 and 8,000 are cleavage products of the protein with an M(r) of 45,000. The full-length protein and the product with an M(r) of 8,000, both of which contain the motif present in double-stranded RNA-binding proteins, bound specifically to double-stranded RNA. The products with M(r)s of 45,000 and 8,000 were also detected in Cowden strain-infected MA104 cells. NSP3 products expressed in COS-1 cells were capable of inhibiting activation of the double-stranded RNA-dependent protein kinase similar to other double-stranded RNA-binding proteins, and NSP3 products expressed in HeLa cells were capable of rescuing the replication of an interferon-sensitive deletion mutant of vaccinia virus.